INSIGHTS INTO HEMATOLOGICAL AND BIOCHEMICAL RESPONSES IN RABBITS: EVALUATING THE SAFETY OF LASER ACUPUNCTURE - Ritonga, Mudhita Zikkrullah; Hidanah, Sri; Lokapirnasari, Widya Paramita (Universitas Syiah Kuala, 2025)
This study aimed to evaluate the effects of laser acupuncture on the hematological profile, total blood cholesterol, and total blood protein in rabbits, with potential applications for livestock. The blood profiles of laser acupuncture-treated rabbits were compared to those of rabbits of the same or different types. Twenty-four New Zealand White rabbits were randomly divided into three groups, with six rabbits in each group. Group One (control/placebo), Group Two (laser acupuncture at specific acupuncture points BL21, BL15, and BL13), and Group Three (laser acupuncture not precisely at acupuncture points). Treatments were administered six times over six weeks. The data presented is the average of the respective data in groups one, two, and three. Results showed that rabbits' hematological profiles, total blood cholesterol, and total blood protein were consistent with existing standards, with no significant deviations observed, indicating that laser acupuncture did not adversely affect rabbit health. These findings suggest that laser acupuncture does not adversely affect rabbit health and could be a safe technique for enhancing animal welfare, with potential applications in livestock management.